2021
DOI: 10.3390/diagnostics11050814
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Left-Atrial Mechanics Assessed by Two-Dimensional Speckle-Tracking Echocardiography to Differentiate Hypertrophic Cardiomyopathy from Hypertensive Left-Ventricular Hypertrophy

Abstract: Hypertrophic cardiomyopathy (HCM) and arterial hypertension (HTN) are conditions with different pathophysiology, but both can result in left-ventricular hypertrophy (LVH). The role of left-atrial (LA) functional changes detected by two-dimensional speckle-tracking echocardiography (STE) in indicating LVH etiology is unknown. Methods: We aimed to characterize LA mechanics using STE in LVH patients with HCM and HTN. LA 2D volumetric and STE parameters were analyzed in 86 LVH patients (43 HCM and 43 isolated HTN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Once vortex generation is impaired, this mechanism could weaken or even disappear. This suggested that myocardial diastolic function appears to be more vulnerable in patients with HCM, in accordance with previous studies [4,22].…”
Section: Non-physiological Vortices In Hcm and H-lvhsupporting
confidence: 92%
See 1 more Smart Citation
“…Once vortex generation is impaired, this mechanism could weaken or even disappear. This suggested that myocardial diastolic function appears to be more vulnerable in patients with HCM, in accordance with previous studies [4,22].…”
Section: Non-physiological Vortices In Hcm and H-lvhsupporting
confidence: 92%
“…Meanwhile, LV ejection fraction is frequently normal and diastolic function is reduced. Speckle-tracking echocardiography and cardiac magnetic resonance (CMR) imaging are often useful to compare early LV structural and LV functional abnormalities in diseases involving ventricular wall thickening [3,4]. Studies have con rmed that early segmental relaxation abnormalities in HCM and H-LVH are different, [5] and compare with HCM cases, the correlation between left ventricular wall thickness and diastolic function is stronger in patients with hypertension [6].…”
Section: Introductionmentioning
confidence: 99%
“…All subjects underwent a comprehensive 2D-transthoracic echocardiography study as previously reported in detail [17]. Echocardiography examinations were performed on VIVID E9 (GE Healthcare, USA) with a 3.5 MHz array probe and images were analyzed o ine on EchoPac, version BT13.…”
Section: Echocardiographic Image Acquisition and Analysismentioning
confidence: 99%
“…Maximal volume (LAVmax) was measured just before mitral valve opening, LA minimum volume (LAVmin) at mitral valve closure, and LA pre-A-wave volume (LAVpre-A), just one frame before atrial contraction in accordance with American Society of Echocardiography and European Association of Cardiovascular Imaging guidelines for chamber quanti cation [19]. Using the above volumes, LA total (LATEV), passive (LAPEV) and active emptying volumes (LAAEV) as well as fractions (LATEF, LAPEF, LAEI and LAAEF) were calculated as shown in a previous paper [17]. The LA stiffness index (LASI) was de ned as E/e′m divided by LASr [20], where E is the mitral E wave velocity and e'm is the average between early-diastolic septal (e's) and lateral (e'l) mitral annular velocities using tissue Doppler imaging (e'm = e'l + e's)/2).…”
Section: Echocardiographic Image Acquisition and Analysismentioning
confidence: 99%
“…Because ATE cats with HCM represented the largest sample within the CATE group, the values for left atrial strain, strain rate, and volume comparing of HCM cats with ATE to the non-CATE and normal groups were quite similar to the results of the CATE group. The pLASRcd of HCM with ATE was significantly less negative than that of the non-CATE group and normal group, suggesting a reduction of LA conduit function similar to human patients with HCM (Popa-Fotea et al, 2021).…”
Section: Two-dimensional Speckle Tracking Echocardiographymentioning
confidence: 77%